Age-Invariant Face Recognition Technique Using Facial Geometry - Osman Ali, A.S. (Springer Verlag, 2013)
While face recognition systems have proven to be sensitive to factors such as illumination and pose, their sensitivity to facial aging effects is yet to be studied. The FRVT (Face Recognition Vendor Test) report estimated a decrease in performance by approximately 5 for each year of age difference. This research study proposed a geometrical model based on multiple triangular features for the purpose of handling the challenge of face age variations that affect the process of face recognition. The system is aim to serve in real time applications were the test images are usually taken in random scales that may not be of the same scale as the probe image, along with orientation, lighting, illumination, and pose variations. Multiple mathematical equations where developed and used in the process of forming distinct subjects clusters. These clusters hold the results of applying the developed mathematical models over the FGNET face aging database. Â© Springer-Verlag Berlin Heidelberg 2013.